La venida del reino: religión, evangelización y cultura en América ; siglos XVI-XX - Ramos, Gabriela; Ramos Cárdenas, Gabriela; Alberro, Solange (Cuadernos para la historia de la evangelización en América Latina, 1994)
"Historical essays exploring the interaction of European Catholicism and native American peoples include considerable archival research while pursuing a diversity of topics"--Handbook of Latin American Studies, v. 58